Survival Analysis of Hospitalized Liver Cirrhotic Patients in Jakarta: 2 Years Follow Up Study - Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2021)
Background: The incidence of liver cirrhosis in Indonesia is increasing over time. In this study, we aim to present a 2-year survival analysis on liver cirrhotic patients using Child-Pugh and MELD score and also analyzing the most common cause of death among liver cirrhotic patients.Method: A retrospective cohort study was used by evaluating the medical records of patients who went to internal medicine ward of Cipto Mangunkusumo Hospital during the period between 2011-2016. The inclusion criteria were all cirrhotic patient registered with a completely filled medical record. The exclusion criteria were the presence of Hepatocellular carcinoma, cholangiocarcinoma, and other form of malignanciesResults: A total of 89 patients were included in this study. The total of 75.3% of the patients were dead during the 2 years follow up with the most prevalent cause of death (COD) being infection (45.5%). Survival analysis, showed that the survival of CP Class A were significantly better than B and C. The cut off value for 2-years mortality was CP score 7 and MELD score 9 in liver cirrhotic patientsConclusion: The mortality rate of liver cirrhotic patients is very high with infection as the main COD. Patients with Child-Pugh score B and C have worse prognosis than Child-Pugh score A.